The first results of using stereotactic vacuum-assisted breast biopsy within breast cancer screening program in State Clinical Hospital of Khanty-Mansiysk - N. A. Zakharova; P. A. Grigoryev; I. P. Gromut; L. F. Grigoryeva; A. V. Filimonov (ABV-press, 2014)
The main aim of this study is to evaluate the results of vacuum-assisted biopsy (VAB) of the breast as a method for further assessment within breast cancer screening program. In State Clinical Hospital 39 women have been undergo VAB after screening mammography during 15 months (2009-2010 years). 5 (13 %) breast cancer cases were detected. Also with VAB were detected 34 patients with local benign changes of the breast, therefore they avoided surgical open biopsy. The using of VAB as a method for further assessment within screening can increase the rate of screen-detected breast cancers at early stage and decrease the number of open surgery biopsy of the breast.